AFIKSASI DERIVASI DAN INFLEKSI PADA ALBUM TAYLOR SWIFT 1989: KAJIAN MORFOLOGI - Irwansyah, NFN; Sofyan, Agus Nero (SUAR BETANG, 2019)
The title of this research is Derivation and Inflection in Taylor Swift?s Album 1989: A Morphology Study. The purpose of this research is to describe types of use of derivation and inflection in the album. This research uses descriptive qualitative method. The paper lies on a theory proposed by O?Grady and Dobrovolsky. Based on the results, the data of derivation divide into six, i.e. noun changes to verbs (2 data), noun changes to adjective (1 data), noun changes to noun (1 data), adjective changes to noun (2 data), adjective changes to adjective (2 data) and derivation of compounding (8 data). In addition, there are 71 data that use the inflection of noun {-s/es}, 28 data inflection of verbs {-s}, 44 data use the {-ing} suffix, 30 data use the {-ed} suffix, 4 data uses the {-er} suffix, 1 data use the {-est} suffix or most and 4 data zero affixations.